2018
DOI: 10.1155/2018/9858921
|View full text |Cite
|
Sign up to set email alerts
|

Microsurgical Reconstruction of the Jaws Using Vascularised Free Flap Technique in Patients with Medication-Related Osteonecrosis: A Systematic Review

Abstract: Background Osteonecrosis of the jaw (ONJ) has been reported to be associated with patients receiving primarily bisphosphonate (BP) therapies. However, lately it has been documented that other medications, such as RANK ligand inhibitor (denosumab) and antiangiogenic drug, can cause ONJ. Micro-osseous-vascular reconstruction of the jaws in patients affected by medication-related osteonecrosis of the jaw represents a viable option of treatment for patients affected by stage III of the disease. However, there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 51 publications
(48 reference statements)
0
24
0
Order By: Relevance
“…This simultaneous therapy is associated with less favourable outcome [10, 17]. The patients who present such a serious stage of MRONJ after concomitant BPs and chemotherapy could be eligible candidates for radical resection of the lesion and reconstruction with microvascular free flaps [18]. It should be highlighted that patients with MRONJ require meticulous preoperative assessment to avoid failure in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This simultaneous therapy is associated with less favourable outcome [10, 17]. The patients who present such a serious stage of MRONJ after concomitant BPs and chemotherapy could be eligible candidates for radical resection of the lesion and reconstruction with microvascular free flaps [18]. It should be highlighted that patients with MRONJ require meticulous preoperative assessment to avoid failure in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, some recent studies have suggested that surgical treatment is more effective and yielded higher patient QOL than nonsurgical treatment 27‐33 . Although surgical treatment is typically recommended for the later stages, the extent of operative treatment remains controversial 28,34,35 . The range of treatment modalities includes the simplest conservative treatment, and when necessary/possible, combined with a sequestrectomy, 36,37 to bony resection of all affected bone, with or without reconstruction with a microvascular free flap 35,36,38,39 …”
Section: Discussionmentioning
confidence: 99%
“…A key focus is the effects of BPs on the oral mucosa, and research in the area includes both 2D and 3D cell culture, and a wide variety of BP effects, including viability, migration, proliferation and adhesion have been studied. This section only reviews articles which have used either pamidronic acid (PA) or zoledronic acid (ZA), as these BPs have been commonly associated with MRONJ development and have the largest body of literature [ 49 , 50 ]. PA has an intermediate anti-resorptive potency, while ZA is one of the highest potency BPs.…”
Section: Bisphosphonatesmentioning
confidence: 99%